2007
DOI: 10.1016/j.indmarman.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Industrial global brand leadership: A capabilities view

Abstract: We examine the global branding programs of five New Zealand industrial firms and identify the salient components and capabilities underpinning these programs. The cases built their respective brand identities around adaptability to customer needs and the provision of a total solution. This identity was built around five capabilities: relational support, coordinating network players, leveraging brand architecture, adding value, and quantifying the intangible. Underpinning these identity promises were five organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 34 publications
4
110
1
Order By: Relevance
“…The findings of this paper are in line with industrial branding authors' recommendations to pursue rich, in-depth and nuanced empirical research in underresearched B2B settings (Beverland et al, 2007;Lynch and Chernatony, 2007;van Riel et al, 2005;Sheth and Sharma, 2006;Wallace and Chernatony, 2007;de Chernatony and Dall'Olmo Riley, 1998).…”
supporting
confidence: 78%
“…The findings of this paper are in line with industrial branding authors' recommendations to pursue rich, in-depth and nuanced empirical research in underresearched B2B settings (Beverland et al, 2007;Lynch and Chernatony, 2007;van Riel et al, 2005;Sheth and Sharma, 2006;Wallace and Chernatony, 2007;de Chernatony and Dall'Olmo Riley, 1998).…”
supporting
confidence: 78%
“…Consistent with recommendations from interpretive researchers (Lincoln & Guba, 1985), grounded theorists (Strauss & Corbin, 1998), and previous case-based research in business-tobusiness marketing (Beverland, Napoli, & Lindgreen, 2007;Flint, Woodruff, & Gardial, 2002), we apply the criteria of credibility, transferability, dependability, confirmability, integrity, fit, understanding, generality, and control. Specifically, we solicit experts to help us select the cases, develop independent interpretations of the findings on an individual basis, and allow respondents to provide feedback on the initial findings.…”
Section: Methodsmentioning
confidence: 99%
“…High brand equity induces customers to pay a premium price for the product or service and to engage in favorable advocacy regarding the firm and its products, thus enhancing its brand performance (Beverland, 2005;Beverland et al, 2007). Hutton (1997) studied professional buyers in the personal computer, fax machine, and floppy disk industries and concluded that there was a brand equity ''halo effect'' transferring brand evaluation from one category to another and that buyers were willing to pay a premium price as well as prepared to buy and recommend products with the same brand name.…”
Section: Industrial Brand Equity and Brand Performancementioning
confidence: 99%